A Nonheroic Cancer Narrative: Body Deterioration, Grief, Disenfranchised Grief, and Growth. (June 2021) - Gabay, Gillie
This longitudinal nonheroic narrative study allows familiarity with personal and societal transitions in the self-identity of individuals with life-threatening cancer. The theoretical anchor is Bion's container–contained theory. Five interviews with a terminally ill hospitalized male in his 30s were conducted along intervals of between 6 and 8 weeks, up to 2 months before his death. Data were analyzed using the selection mechanisms method. Findings provide insights about the hospitalization experience, his grief, and disenfranchised grief. A rigid mode of container–contained relationships with clinicians created disenfranchised grief. Reflection and coherence among self-identities lead to inner strength and emotional growth despite the body's deterioration. Clinicians have a role in holistic identity transitions of individuals with cancer. Findings illuminate practical recommendations that clinicians may adopt to improve the experience of individuals suffering from cancer at the chronic and terminal phase of illness.